Multiple Product Costing by Multiple Correlation Analysis. - Chiu, John S.; DeCoster, Don T. (The Accounting Review, 1966)
Abstract The article focuses on the application of multiple correlation analysis in multiple product costing. The allocation of costs assumes that the products should receive costs relative to the benefits that the products received from the production process. The authors conclude that multiple correlation analysis frees the accountant from making the assumption that marginal costs per product are always too difficult to unearth. For products that have an output proportion that is variable, multiple correlation allocates costs in a method valuable for decision-making.